Interpreting ‭ד א‬ in Genesis 2.5-6: Neglected Rabbinic and Intertextual Evidence - Rogland, Max (Journal for the study of the Old Testament, 2010)
This article seeks to clarify the semantics of Hebrew ‭ד א‬ by drawing attention to two factors: specifically, the usage of the word in Rabbinic Hebrew and the phenomenon of biblical intertextuality. A number of Rabbinic passages are examined which indicate that the word ‭ד א‬ was understood as a cloud of some kind. This understanding of ‭ד א‬ is also observable in intertextual references to Gen. 2.5-6 in Ps. 135.7 and Jer. 10.13. Such evidence confirms the Targumic tradition, which renders Hebrew ‭ד א‬ as ‘cloud’. The article concludes with exegetical and grammatical remarks on Gen. 2.5-6 in light of this understanding of ‭ד א‬.